O Cancioneiro Caipira De Elpídio Dos Santos: Apresentação, Comentário E Antologia - Almeida, Alexandre Rezende De [UNIFESP] (2018)
This Research Deals With The Compositional Universe Of Elpídio Dos Santos (1909-1970), With A Focus On The Caipira Song Genre, An Area In Which This Composer Got Most Recognition During His Musical Trajectory. Over Four Decades Of Activity, He Created About A Thousand Works In A Lot Of Different Genres, Including Among The Main Ones: Caipira, Samba, Choro, Waltz, Baião, Marchinha And Samba-Canção, Although Only About Seventy Songs Have Been Recorded. Elpídio Dos Santos Became Famous Mainly Between The Decades Of 1950 And 1960 When He Composed Diverse Musical Tracks For Mazzaropi"S Movies, Thus Santos Became His Favorite Composer For That Work. Most Of Elpídio's Work Is Still Unexplored, For This Reason, The Composer's Unpublished Caipira Songbook Has Appeared As A Significant Object To Be Researched In This Work. A Search Was Made In His Original Records, Which Was Kindly Authorized By Maria Aparecida Dos Santos, One Of His Daughters, Responsible For Maintaining The Collection. In Elpídio's Collection, Letter